Bandwidth optimization of ultra-wideband (UWB) antenna - Ulusow, Shafi’i Mo’allim Ali (2013)
This project presents the design with optimum geometry of an UWB rectangular patch antenna. To achieve an UWB characteristic, a patch antenna is designed before proceeding to the bandwidth optimization technique for the proposed antenna. The configuration of patch antenna has a partial ground and addition of two steps in the bottom edge of the patch and one slot in the middle of the patch. The antenna was designed and optimized using CST Microwave Studio (CSTMWS). The proposed antenna’s parameters were optimized with various options such as differing the ground plane length, differing the width of feed line, with different slot positions and different slot widths, and found to operate satisfactorily. An optimized bandwidth has been noticed in this design. Moreover, the antennas structure offers great advantages due to its simple designs and small dimensions. The antenna has been fabricated using FR-4 substrate and tested using the network analyzer which has range between to 3GHz to 13GHz at the Radio Frequency (RF) Laboratory. The antenna performance showed agreement between both simulation and measurement results with only some small deviation and this observed deviation is due to the different numerical modeling and meshing techniques.